Efficacy of Aprotinin in Reducing Blood Loss in Paediatric Patients Undergoing Major Spinal Surgery - Greenfield, Hayley M.; Colovic, Vesna; Gharib, Maged I.; Rushman, Sarah; Patel, Davendra K.; Will, Andrew M.; Walker, Robert W.M. (Blood, 2004)
Blood loss during corrective surgery for scoliosis and the requirement for homologous blood is an important issue in paediatric spinal surgery. This is particularly pertinent in cases of scoliosis secondary to underlying neuromuscular disease where anaemia may be less well tolerated, both intra-operatively and post-operatively, due to multiple organ dysfunction. Despite the introduction of techniques to minimise the necessity to transfuse homologous blood (pre-deposit autologous donation, cell salvage and isovolaemic haemodilution), it is often required. This brings with it the potential risks of allo-immunization and infective complications. In the UK homologous blood is an increasingly precious resource following the recent exclusion of donors who have themselves received blood products in the last ten years in view of the potential risk of new variant CJD. Aprotinin, a serine proteinase inhibitor (now produced by recombinant technology) with antifibrinolytic properties and the ability to preserve platelet function has been shown to reduce blood loss in major cardiac surgery and liver transplantation. Its effectiveness in the orthopaedic setting has generated more varied reports, however in the setting of spinal surgery for idiopathic scoliosis it has recently been shown to reduce intra-operative blood loss and the requirement for homologous transfusion. We report here our experience with the use of aprotinin in a group of paediatric patients undergoing surgery for scoliosis secondary to an underlying neuromuscular disorder and its effect on intra-operative blood loss. 33 successive patients referred to our institution were allocated to receive aprotinin (n=18) or not (n=15). For those who received the drug a test dose of 50,000KIU was followed by a loading dose of 10,000KIU/kg over 30 minutes. A maintenance infusion was set up at 5,000KIU/hour for the duration of the procedure. The demographics of the two groups were not significantly different. The median age of those children receiving aprotinin was 12 years (7–15) and those who did not 13 years (7–17), [p=0.09]. The median weight of the children receiving aprotinin was 40kg (25–55) and those who did not 38.5kg (21–55), [p=0.74]. The procedures undertaken were posterior spinal fusion (n=26), anterior and posterior fusion (n=3), insertion of growing rods (n=2) and correction of kyphoscoliosis (n=2). All procedures were performed by one of three consultants. The operative time in the two groups was not significantly different, 6.5 hours (4.1–8.9) in those who received aprotinin and 5.7 (4.4–7) in those who did not [p=0.54]. There was however a significant reduction in blood loss in the group who received aprotinin, with an average reduction of 51.6%. Median losses for those who received aprotinin were 1380ml (380ml–2380ml) and 2849ml (1047ml–4651ml) for those who did not [p=0.01]. No adverse events in the form of allergic reactions were observed in the children who received the drug. We conclude that aptotinin is a safe and effective pharmacological intervention which can be used in spinal surgery to reduce operative blood loss. This should translate into a reduced requirement for homologous blood although this was not determined in this study. Evaluation of this secondary endpoint is ongoing.